Neutrophil gelatinase-associated lipocalin is a predictor of complications in the early phase of ST-elevation myocardial infarction - Nirvana Šabanović-Bajramović; Enisa Hodžić; Amer Iglica; Edin Begić; Nerma Resić; Kenana Aganović; Mirela Halilčević; Senad Bajramović (Medicinski glasnik, 2020)
Aim: To evaluate a correlation of serum level of neutrophil gelatinase-associated lipocalin (NGAL) to the risk of the occurrence of complications in patients with the early phase of ST-segment elevation myocardical infarction (STEMI) treated with fibrinolytic therapy prior to percutaneous coronary intervention (PCI). Methods: A total of 54 patients with the diagnosis of STEMI treated with fibrinolytic therapy (alteplase) prior to PCI were included. Patients were admitted to the Intensive Care Unit (ICU) of Clinic for Heart, Blood Vessel and Rheumatic Diseases in the period January to March 2018. All patients underwent coronary angiography and PCI within the maximum of 48 hours delay after fibrinolysis, according to the hemodynamic and electrical stability and PCI availability. Blood samples were taken immediately after admission prior to fibrinolytic administration. Patients were divided into two groups according to NGAL values (less or more than 134.05 ng/mL). Results: Higher values of NGAL have effect on a higher mean systolic and diastolic pressure (p=0.001 and p=0.003, respectively). Patients with higher NGAL values also have higher values of brain natriuretic peptide (p=0.0001) and highly sensitive troponin I (p=0.002). In that group relative risk (RR) for lethal outcome was 6.4 times significantly higher (p=0.002), for the development of heart failure 2.88 times (p=0.0002), for post-myocardial infarction angina pectoris 2.24 times (p=0.0158), and for ventricular rhythm disturbances (ventricular tachycardia, ventricular fibrillation) 1.96 times higher (p=0.0108). Conclusion: Increased NGAL value is related to an unfavourable outcome of patients in the early phase of STEMI treated with fibrinolytic therapy prior to PCI.
Keywords: acute coronary syndrome; lipocalin-2; prognosis